The Influence of Brand Image and Restaurant Attributes towards Customer Satisfaction at Pekkio Restaurant: The Influence of Brand Image and Restaurant Attributes towards Customer Satisfaction at Pekkio Restaurant - Marcella, Oei Natalia; Christian, Sonata (Jurnal Entrepreneur dan Entrepreneurship, 2020)
In this globalization era, food service industry as restaurant that provide the basic of human needs has been well developed. The development of food industry has given a huge contribution to the social and environment aspects (Franceschelli et al, 2018). Pekkio restaurant is one of the restaurants in Surabaya that sell Singapore chinese cuisine in Pakuwon Mall Surabaya. In order to survive in this industry, Pekkio restaurant continuously develop their performance to increase the customer satisfaction. With the purpose to find out the factors that influence customer satisfaction, this research aims to discover whether brand image, food quality, service quality, and atmospherics have significant influence towards customer satisfaction of Pekkio restaurant. Therefore, researcher conducted an online survey that are distributed to the samples using 5-point Likert-scale. The population is unknown thus, the researcher use special method from Roa (2016) and the sample become 97. Moreover, the obtained data will be analysed using Multiple Linear Regression. The result shows that food quality and service quality have significant influence towards customer satisfaction of Pekkio restaurant. However, brand image and atmospherics don’t significantly influence customer satisfaction at Pekkio restaurant . Albeit, there are positive relationship of brand image and atmospherics towards customer satisfaction of Pekkio restaurant. Keywords: Brand Image, Food Quality, Service Quality, Atmospherics, and Customer Satisfaction